2011 IEEE First International Conference on Healthcare Informatics, Imaging and Systems Biology 2011
DOI: 10.1109/hisb.2011.2
|View full text |Cite
|
Sign up to set email alerts
|

3G Smartphone Technologies for Generating Personal Social Network Contact Distributions and Graphs

Abstract: This paper presents a novel means of collecting and analyzing data related to personal social contact networks. The work developed a custom application for Smartphones that support Bluetooth connectivity, as representative of the ensemble of many consumer electronic products and can be used to infer users' proximity, contact duration, and GPSbased information. In many cases this is augmented by device meta identity. The 3G application, data storage and retrieval is discussed in detail. Preliminary data were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…In contrast, our study found differences in multiple contact-structure metrics by school and grade range, including higher modularity, clustering, and mean contact duration in lower-level schools compared to higher-level grades. In [ 26 ], the authors also found power-law distributed contact and encounter durations as well as another study [ 45 ] in which phones with Bluetooth technology was used instead of sensor motes. In [ 45 ], the statistical fit of contact duration distributions gave a power-law exponent of -1.33, within the range we found for different schools, -0.9 to -1.4.…”
Section: Discussionmentioning
confidence: 89%
“…In contrast, our study found differences in multiple contact-structure metrics by school and grade range, including higher modularity, clustering, and mean contact duration in lower-level schools compared to higher-level grades. In [ 26 ], the authors also found power-law distributed contact and encounter durations as well as another study [ 45 ] in which phones with Bluetooth technology was used instead of sensor motes. In [ 45 ], the statistical fit of contact duration distributions gave a power-law exponent of -1.33, within the range we found for different schools, -0.9 to -1.4.…”
Section: Discussionmentioning
confidence: 89%
“…Technological advances and the continuous development of new software and sensors that provide high-quality location, proximity, visual, auditory data, and face and voice recognition systems are ongoing processes (see Benavides et al, 2011;Choudhury, 2004;Elrefaei, Alharthi, Alamoudi, Almutairi, & Al-Rammah, 2017;Niu, Wang, & Lu, 2015). Thus, future possibilities that could provide additional data include the integration of measures from external sensors: for example, sensors capable of measuring biological signals (e.g., heartbeat, skin-resistance, gait, etc.…”
Section: Future Directionsmentioning
confidence: 99%
“…Technological advances and the continuous development of new software and sensors that provide high-quality location, proximity, visual, auditory data, and face and voice recognition systems are ongoing processes (see Benavides et al, 2011;Choudhury, 2004;Elrefaei, Alharthi, Alamoudi, Almutairi, & Al-Rammah, 2017;Niu, Wang, & Lu, 2015). Thus, future possibilities that could provide additional data include the integration of measures from external sensors: for example, sensors capable of measuring biological signals (e.g., heartbeat, skin-resistance, gait, etc.…”
Section: Future Directionsmentioning
confidence: 99%